Assessment of male reproductive traits in endangered leuciscids from the Iberian Peninsula: First attempts to store gametes both at short- and long-term - Hernández-Rodríguez, Ana (2023)
During the spring of 2022, several endangered leuciscid species (Anaecypris hispanica, Squalius aradensis, Anachondrostoma Occidentale, and Iberochondrostoma lusitanicum) were sampled both at the Vasco da Gama aquarium facilities and in some rivers of the Algarve region, Portugal. Sperm samples were extracted by gentle abdominal pressure and sperm motion parameters were assessed for the frst time in four species, using a computerized analysis system. The results obtained showed that spermatozoa kinetic patterns were similar for all 4 species, with high motility and velocity values after the sperm activation time and with a marked decrease after 20. On the other hand, sperm longevity was highly variable between species, with short longevities (around 40 s) for A. hispanica and S. aradensis, and longer ex situ breeding programs that are being developed for these four endangered species